Editorial - Guillen Uyen, Jorge (2019)
We would like to present the 47th issue of the Journal of Economics, Finance and Administrative Science, the first issue of 2019. Our journal is now receiving the best rating of citations according to the Scielo database, which locates it in the 88th percentile. According to new requirements for journals indexed in prestigious databases, we have increased the number of papers starting in this issue. The first article, entitled “The determinants of conventional banks profitability in developing and underdeveloped OIC countries” investigates the effect of internal and external variables on the profitability of conventional banks operating on developing and underdeveloped countries, the Organization of Islamic Cooperation (OIC) states. Doi:  https://doi.org/10.1108/JEFAS-06-2019-128